2017
DOI: 10.1590/1981-22562017020.170086
|View full text |Cite
|
Sign up to set email alerts
|

Timed Up and Go test as a sarcopenia screening tool in home-dwelling elderly persons

Abstract: Objective: to evaluate the performance of the Timed Up and Go test (TUG) as a screening tool for sarcopenia in elderly persons living in a city in the south of Brazil. Method: A cross-sectional, home-based study was conducted with 322 elderly persons. The diagnosis of sarcopenia was based on the criteria proposed by the European Working Group on Sarcopenia in Older People (EGWSOP). A Receiver Operating Characteristic (ROC) curve was constructed to assess the discriminatory power of the TUG on sarcopenia screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 10 publications
0
12
0
5
Order By: Relevance
“…TUG assesses an individual's mobility, which requires static and dynamic balance. Prior studies have shown that TUG is a good screening tool for sarcopenia among hospitalized older patients and home‐dwelling older adults . Furthermore, AGE is an independent factor of low SMI among middle‐aged and older adults .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…TUG assesses an individual's mobility, which requires static and dynamic balance. Prior studies have shown that TUG is a good screening tool for sarcopenia among hospitalized older patients and home‐dwelling older adults . Furthermore, AGE is an independent factor of low SMI among middle‐aged and older adults .…”
Section: Discussionmentioning
confidence: 94%
“…Prior studies have shown that TUG is a good screening tool for sarcopenia among hospitalized older patients and home-dwelling older adults. 18,19 Furthermore, AGE is an independent factor of low SMI among middle-aged and older adults. 20 An experimental study found that mice with high AGE diet showed CML accumulation in their extensor digitorum longus muscle and low muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…Like Pinheiro et al 27 , Fillippin et al 29 carried out another study in 2017 showing good results for the physical tests in the detection of sarcopenia. In this study, the performance measure used to predict sarcopenia in a population of old people of both genders was the Timed Up and Go (TUG) test, which presented adequate sensitivity for the prediction of sarcopenia and screening of the condition.…”
Section: Discussionmentioning
confidence: 98%
“…TheTUG(Timed Up and Go test) is a simpletestused to assess a person's mobility and requires both static and dynamic balance [28].The TUG test was used to assessparticipants' sarcopenia risk. A cut-off point of 7.5 s, with 88.9% sensitivity, 31.4% specificity was considered for risk of sarcopenia [28].…”
Section: Assessment Of Sarcopeniamentioning
confidence: 99%